2013
DOI: 10.1089/jmf.2013.2784
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Body Weight and Fat and Improved Lipid Profiles in Obese Rats Fed Apple Pomace or Apple Juice Concentrate

Abstract: The purpose of this study was to investigate the influence of apple pomace (AP) and apple juice concentrate (AC) supplementation on body weight and fat loss as well as lipid metabolism in obese rats fed a high-fat diet. Diet-induced obese rats were assigned to three groups (n = 8 for each group): high fat diet (HFD) control, HFD containing 10% (w/w) AP, and HFD containing 10% (w/w) AC. There was also a normal diet group (n = 8). After 5 weeks, body weight gain, adipose tissue weight, serum and hepatic lipid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 40 publications
4
31
2
1
Order By: Relevance
“…On the other hand, increased adipose tissue volume can also increase body weight gain. A study by Cho et al (22) reported that the HFD experimental group had the highest level of LDL, total cholesterol and triglyceride, but the lowest levels of HDL. Consumption of HFD causes increased fatty acid synthesis in the liver that results in lipid accumulation that disrupts metabolic homeostasis in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, increased adipose tissue volume can also increase body weight gain. A study by Cho et al (22) reported that the HFD experimental group had the highest level of LDL, total cholesterol and triglyceride, but the lowest levels of HDL. Consumption of HFD causes increased fatty acid synthesis in the liver that results in lipid accumulation that disrupts metabolic homeostasis in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have confirmed this trend in animal models, Cho [12] testing pome apple (PA) and apple juice concentrate (AJC) on different groups with a high fat diet. They found that the groups which were supplied with PA and AJC in the presence of high-fat diet had a lower weight, lower total CHOL, lower CHOL LDL, while CHOL HDL was significantly higher in the PA group compared with AJC.…”
Section: Fo) Fuji Skin (Fp) Traditional Fuji (Tf) Organic Granny Smentioning
confidence: 80%
“…Different apple extracts have been reported to decrease the weight of visceral adipose tissue as compared to controls. Furthermore it has been found that diets supplemented with apple skin have a positive effect on the lipid profile [12] [13]. However, there is insufficient scientific evidence to determine if the source apple extracts such as traditionally or organically managed orchards, as well as green or red fruits and apple skin from by-product of agroindustry or discarded in the orchard have a better result in the lipid profile [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…clorogénico eq./g) y fresas (3,63 mg ác. clorogénico eq./g), que son frutos que se caracterizan por tener un alto contenido fenólico (17) .…”
Section: Discussionunclassified